2008
DOI: 10.1186/1477-7819-6-137
|View full text |Cite
|
Sign up to set email alerts
|

A rare tumoral combination, synchronous lung adenocarcinoma and mantle cell lymphoma of the pleura

Abstract: Background: Coexistence of adenocarcinoma and mantle cell lymphoma in the same or different anatomical sites is extremely rare. We present a case of incidental discovery of primary lung adenocarcinoma and mantle cell lymphoma involving the pleura, during an axillary thoracotomy performed for a benign condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…As such primary pleural lymphoma was reported previously, we speculated that the right pleura could have been the site of origin of MCL in the second case. Indeed, Hatzibougias et al (16) reported a case of MCL that developed from the pleura. The disease was discovered incidentally during an operation for pneumothorax.…”
Section: Chemotherapy (A) Both Tumors Disappeared After Chemotherapymentioning
confidence: 99%
“…As such primary pleural lymphoma was reported previously, we speculated that the right pleura could have been the site of origin of MCL in the second case. Indeed, Hatzibougias et al (16) reported a case of MCL that developed from the pleura. The disease was discovered incidentally during an operation for pneumothorax.…”
Section: Chemotherapy (A) Both Tumors Disappeared After Chemotherapymentioning
confidence: 99%
“…Synchronous development of these two tumors is one of the most challenging problems in diagnosis and treatment. The therapeutic management of such a combination of tumors requires separate consideration of their biologic behavior, the performance status of each patient individually and the estimated morbidity related to surgery and/or chemoradiotherapy . In our case, a first mediastinoscopy was realized to determinate if the mediastinal adenopathies correspond to mantle cell lymphoma or metastasis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…Hatzibougias et al . reported a synchronous lung adenocarcinoma and mantle cell lymphoma of the pleura and only one case of synchronous existence of nodal mantle cell lymphoma and metastatic in mediastinal lymph nodes small cell lung carcinoma was reported by Kampalath et al . .…”
Section: Discussionmentioning
confidence: 99%
“…The presented case is the first one reported in the literature with synchronous BALT lymphoma of the lung and squamous cell lung cancer, in different lungs of the same patient. Reviewing the literature, we were able to find 6 case reports with synchronous BALT lymphoma and lung adenocarcinoma [35], one case with coexistence of lung adenocarcinoma with mantle cell lymphoma of the pleura [6], and one case with synchronous lung cancer (nonspecified) with tracheal mucosa-associated lymphoid tissue (MALT) lymphoma [7]. …”
Section: Discussionmentioning
confidence: 99%